Demographic Factors and the Social Welfare of Stranded Individuals in South Sumatra - Amaliyah, Rizki; Sianturi, Maria Paulin (Yayasan Rumah Ilmu Professor, 2025)
This qualitative study examines the demographic factors influencing the social welfare of stranded individuals handled by the Social Services Agency of South Sumatra Province. Data was collected through a triangulation of observation, interview, and documentation methods. The research findings indicate that the primary causes of being stranded are economic, manifesting in three main ways: running out of travel funds, being victims of pickpocketing, and employment fraud. It was found that the majority of stranded individuals originate from provinces with high unemployment and poverty rates, such as Central Java, East Java, West Java, and North Sumatra. Age, gender, education level, and informal employment status were identified as significant demographic variables that increase an individual's vulnerability. Their social welfare condition is generally low, characterized by a deficit in meeting basic needs, physical health problems, psychological distress in the form of stigma and anxiety, and minimal social integration. The Social Services Agency plays a crucial role in providing emergency assistance and facilitating repatriation, but these curative measures have not fully addressed the root problems. This phenomenon confirms that being stranded is a multidimensional issue requiring a preventive and collaborative approach.